Relationship between grain-boundary capacitance and bulk shallow donors in SnO2 polycrystalline semiconductor - Bueno, Paulo Roberto [UNESP]; Santos, M. A. [UNESP]; Ramirez, M. A. [UNESP]; Tararam, R. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley-v C H Verlag Gmbh, 2008)
The relationship between grain-boundary capacitance and extrinsic shallow donors caused by Nb addition to SnO2 center dot COO binary polycrystalline system has been investigated by means of combined techniques such as I-V characteristic response, complex impedance and capacitance analysis and electrostatic force microscopy. The estimated role of the Nb doping is to increase the concentration of shallow donors that are capable of enhancing the electronic donation to grain-boundary acceptors. This effect leads to the formation of potential barriers at grain boundaries with a simultaneous increase of grain-boundary capacitance and non-Ohmic features of the polycrystalline device doped with Nb atoms.